DAMPAK PEMUTUSAN HUBUNGAN KERJA SELAMA PANDEMI COVID-19 PERSPEKTIF HUKUM KETENAGAKERJAAN - Suci Flambonita (Keadilan : Jurnal Fakultas Hukum Universitas Tulang Bawang, 2020)
Research shows a wave of layoffs and a decrease in labor/employee/employee income during the COVID-19 pandemic. The percentage of dismissed workers/employees/employees in Indonesia at the end of April 2020 was 15.6%. Based on data obtained by the South Sumatra Regional Office of Manpower and Transmigration on April 29, 2020, as many as 612 workers in South Sumatra experienced layoffs due to the COVID-19 pandemic. A total of 7,020 workers were laid off and received no wages during the pandemic. The research method used is socio legal research, namely research that examines the social symptoms that exist in society and then correlates them with statutory regulations. The impact of layoffs during this pandemic, many of these companies often use force majeure reasons. On the other hand, to tackle the Covid-19 problem, one of the efforts made by the Government is the Circular of the Minister of Manpower Number M/3/HK04/II/2020 concerning Protection of Workers/Laborers and Business Continuity in the Context of Preventing and Overcoming Covid-19. Some companies that cut off work relations during the COVID-19 pandemic often use force majeure reasons, to avoid wages and severance pay that should be the rights of workers/laborers.